Matrine Attenuates D-Galactose-Induced Aging-Related Behavior in Mice via Inhibition of Cellular Senescence and Oxidative Stress. (27th November 2018) - Sun, Kaiyue; Yang, Pengyu; Zhao, Rong; Bai, Yuting; Guo, Zijiao
Abstract : The present study was designed to evaluate the effects of matrine (MAT) on D-galactose- (D-gal-) induced aging and relative mechanism. Vitamin E at the dose of 100 mg/kg was used as a standard positive control. MAT significantly improved the D-gal-induced recognition and spatial memory impairment in novel object recognition and Y maze tests, and exercise endurance decreased in the weight-loaded swimming test at 2 and 10 mg/kg. We found that D-gal treatment induced noticeably aging-related changes such as reducing thymus coefficients, increasing the pathological injury and cellular senescence of liver, spleen, and hippocampus, as well as an increase in cyclin-dependent kinase inhibitor p16, p19, and p21 gene expression and the interleukin -1β expression in the liver and hippocampus. MAT showed effective protection on such changes. Furthermore, MAT decreased the oxidative stress of the liver, plasma, and brain, as evidenced by increased total antioxidant capacity, total superoxide dismutase, and catalase activities and decreased the malondialdehyde level. Additionally, there was a significant positive correlation between swimming time in weight-loaded swimming time and thymus index. MAT ameliorated aging-related disorder caused by D-gal through the inhibition of both cellular senescence and oxidative stress. The study provides further evidence for drug development of MAT for prevention or treatment of the aging-associated disorder.